Leveraging AI in Healthcare: Insights from Petroleum Industry Practices and Fraud Detection Strategies with ChatGPT Applications - Muhammad Ibrar; Muhammad Fahad; Muhammad Umer Qayyum; Ali Husnain (CV. Shofanah Media Berkah, 2024)
Healthcare is changing quickly because to advances in artificial intelligence (AI) that improve patient care, diagnosis, and treatment. In order to give readers a thorough grasp of the potential advantages and difficulties of artificial intelligence (AI), this paper examines the various uses of AI in healthcare and draws comparisons with its use in other industries, such as the petroleum industry. AI's effects on healthcare include better patient care through real-time monitoring and AI-powered virtual assistants, personalized medicine through customized treatment programs, and increased diagnostic accuracy through sophisticated image analysis. These developments aid in addressing important healthcare concerns like the effectiveness of individualized treatment plans and delays in diagnosis. Healthcare can learn a lot from the petroleum industry, which is well-known for its intricate and data-intensive processes. The application of AI to healthcare problems is exemplified by the petroleum industry, which uses predictive maintenance, real-time monitoring, optimization algorithms, and data integration. In the healthcare industry, real-time monitoring and predictive analytics can enhance patient outcomes by foreseeing problems and successfully managing chronic illnesses. Algorithms for optimization can also improve hospital operations and resource management, and data integration can improve decision-making by providing thorough patient insights. ChatGPT and other AI models have shown promise in transforming healthcare decision support and communication. These models support clinical documentation, improve administrative efficiency, and enable better patient-provider interactions. To fully exploit the benefits of AI, however, obstacles including data privacy, integrating AI with current systems, and correcting biases must be overcome. The prospects for healthcare to embrace similar technology to enhance its capabilities are highlighted by the cross-industry insights obtained from AI applications in the petroleum business. Notwithstanding AI's potential, its effective application necessitates resolving issues with data security, system integration, and morality. Healthcare will be shaped in the future by the substantial gains in patient outcomes, operational effectiveness, and care quality that AI technology is expected to bring about as it develops.